THE IMPACT OF QUALITY, VISIONARY, AND ENTREPRENEURIAL LEADERSHIP OF VOCATIONAL SCHOOL PRINCIPALS ON THE SUCCESS OF SCHOOL MANAGEMENT - SUPRIYANTO, SIDIQ; Gilang Purnomo, Bayu; Amiruddin, Muhamad (Universitas Negeri Semarang, 2025)
This study investigates the influence of school principals’ leadership styles, specifically quality leadership, visionary leadership, and entrepreneurial leadership, on the success of school management in Vocational Schools specialising in Technology and Engineering in Yogyakarta. Employing a descriptive quantitative approach with an ex-post facto design, data were gathered from 282 teachers selected through cluster sampling and stratified random sampling across 16 Vocational schools of various accreditation levels. The results reveal significant positive influences of quality leadership (31.5%), visionary leadership (11.1%), and entrepreneurial leadership (35.7%) on school management success. Simultaneously, the combined leadership styles contributed 37.3% to the variance in management success. These findings highlight the importance of multifaceted leadership in improving educational outcomes and suggest the need for policy reinforcement to support effective school governance.